Ikd Current in Cold Transduction and Damage-Triggered Cold Hypersensitivity - Ugarte-Martinez, G; Madrid-Montecinos, R; Gonzalez-Figueroa, A; Pertusa-Pastor, M; Piña-Muñoz, R (Springer New York LLC, 2017)
In primary sensory neurons of the spinal and trigeminal somatosensory system, cold-sensitivity is strongly dependent on the functional balance between TRPM8 channels, the main molecular entity responsible for the cold-activated excitatory current, and Shaker-like Kv1.1-1.2 potassium channels, the molecular counterpart underlying the excitability brake current IKD. This slow-inactivating outward K+ current reduces the excitability of cold thermoreceptor neurons increasing their thermal threshold, and prevents unspecific activation by cold of neurons of other somatosensory modalities. Here we examine the main biophysical properties of this current in primary sensory neurons, its central role in cold thermotransduction, and its contribution to alterations in cold sensitivity triggered by peripheral nerve damage. © Springer International Publishing AG 2017.